Pelatihan dan Pendampingan Pembuatan Artikel Ilmiah Berbasis AI untuk Meningkatkan Keterampilan Menulis Calon Guru - Masjudin Masjudin; Yuntawati Yuntawati; Sabrun Sabrun; Ita Chairun Nissa; Ahmad Muzaki (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
Training and assistance in the creation of scientific articles based on artificial intelligence (AI) aims to improve the scientific writing skills of prospective teachers at Mandalika Education University. The program involves the use of AI-based tools such as ChatGPT to correct grammar and Scite AI to help participants find relevant references quickly. A total of 25 students of the Faculty of Science, Engineering, and Applied participated in this training online. The method used in this activity involves three main stages, namely preparation, training, and mentoring. In the preparation stage, the training materials are designed to cover important topics related to scientific writing, the use of AI-based tools, and reference management using Mendeley and Zotero. The training was carried out in the form of interactive sessions, where participants were given material on the structure of scientific articles, the use of AI tools, and reference management techniques. Mentoring is carried out individually to provide more specific feedback on the articles that have been compiled by the participants. The results of the evaluation showed a significant improvement in the participants' ability to understand the structure of scientific articles using academic language, and to manage references appropriately. Despite the challenges associated with academic integrity and reliance on technology, this training provides a solid foundation for aspiring teachers to integrate technology in scientific writing and teaching.